Meningiomas and the tumor microenvironment: expression of PD-L1 and expression of PD-L1 and interferon-gamma in the prognosis - Gunter Gerson; Paulo G. B. Silva; Carlos Eduardo L. Soares; Gabriel C. L. Chagas; Amanda R. Rangel; Aline K. A. Rodrigues; Cleto D. Nogueira; Fábio R. F. Távora
ABSTRACT Introduction: Meningiomas are the most common intracranial tumors in adults. One of the mechanisms used by tumor cells to escape death by immune cells is to interfere with immunological checkpoints, thereby preventing the establishment of adequate immune response. Following this concept, a promising target for an immunomodulatory therapy is blocking programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1 axis), which is known to be crucial for immune escape mechanisms. Interferon-gamma (IFN-γ) is related to PD-L1 expression, produced by activated T cells, and may promote hyper-regulation of PD-L1 expression in tumor cells. Methods: The retrospective cross-sectional cohort study analyzed 93 patients diagnosed with meningioma of different degrees, and immunohistochemical reactions of PD-L1 and IFN-γ proteins were performed. Results: This study did not detect PD-L1 immunoexpression in any of the 93 analyzed cases. The PD-L1 expression in meningioma cells and their potential role in local immunosuppression are not fully established and their indication for anti-PD-L1 therapy as an alternative treatment for meningiomas is still controversial. Conclusion: IFN-γ immunoexpression was related to lower rates of tumor recurrence and longer progression-free survival time; there was also a relationship with the absence of pleomorphism, better differentiation and lower tumor grade for this marker.